Trajetória curricular da disciplina de Ciências Humanas e Sociais nos cursos de Engenharia de uma Universidade Federal - Guimarães, Giovanni Horácio (2015)
This work completes a doctoral research, conducted at the Graduate Studies Program in Education: Curriculum, part of the Pontifícia Universidade Católica de São Paulo, in the period between 2010 and 2014. The object of this investigation was established to be the curricular trajectory of the discipline "Social and Human Sciences" in the engineering courses at the Federal University of Itajubá, their disciplinary arrangements and programmatic directions acquired since its implementation in 1998. The main objective was to reassemble characteristics of the curricular trajectory of the discipline of "Human and Social Sciences" at the Federal University of Itajubá Engineering by recovering evidence of its disciplinary arrangement, its relations with the modifications imposed by the laws that regulate engineering education, its faculty, its contents and practices. The research scenario was the Federal University of Itajubá, located in the south of Minas Gerais. An institution of higher education founded in 1913 from the initiative of a positivist lawyer, Theodomiro Carneiro Santiago, as Institute of Electrical and Mechanical Engineering of Itajubá. It became a federal institution in 1956 and its name was changed to Federal School of Engineering of Itajubá in 1968. Finally it became Federal University of Itajubá in 2002. In this sense, a qualitative approach was carried out and non-directive interviews, oral history and historical and documentary analyses were used as research procedures. The subjects are four professors of the institution who have taught Human Sciences since 1998. The path chosen to elaborate the theoretical reference was the curriculum mapping in its multidimensionality; the location of the theme of educational disciplining knowledge within the curriculum studies; the limits of curricular dimensions of school subjects; the pointing of relations between disciplining and teaching practice. The main theoretical references of this study are the works of Andre Chervel (1990), Apple (2008), Forquin (1993), Gimeno Sacristán (1999 and 2007), Goodson (1996 and 2008), Moreira & Silva (1996) and Viñao (2008). Fulfilling its goal, the research rescued pre-specified dimensions of the discipline; mapped important features of the faculty, such as academic production, their theoretical areas, traces of their practices and professorial identity. Also, it pointed out new paths to be investigated on the object